Complicações na estomia intestinal de eliminação e pele periestomia: processo de (in) adaptação à luz de Roy - Bavaresco, Marina (2020)
The making of an intestinal elimination stoma results in the diversion of intestinal transit to the abdomen. In the process of adapting to the new condition, several adaptive problems may arise and negatively influence the person's quality of life, such as the appearance of complications in the ostomy and peristomy skin. Thus, the objective of the present study was to understand the adaptation process of the person with intestinal ostomy and complications in the ostomy and / or peristomy skin in the light of Callista Roy's Theory. This is a qualitative research with content analysis by Bardin, anchored in the Theory of Adaptation by Callista Roy, carried out at the home of 12 people with intestinal ostomy and complications in the ostomy and / or peristomy skin. The techniques of interview, non-participant observation and field diary were used. The study was approved by the Research Ethics Committee of the Federal University of Alfenas, under opinion No. 3,071,507. From the analysis of the data, it was possible to characterize the sociodemographic and clinical features, the description of complications in the ostomy and / or peristomy skin and the elaboration of categories related to the physiological adaptive modes, self-concept, function in real life and interdependence. Complications in ostomy and / or ostomy skin are linked to adaptation problems in the physiological mode, and can act as an influencing agent in other modes. The presence of complications, more than producing non-adapted behaviors, may indicate failures in the process of adaptation to the ostomy, therefore, they can be characterized as a result of failure in this process and, consequently, become stimuli for other unsuitable behaviors, in a complex cycle. Thus, the adaptation process of the person with an ostomy and complications in the ostomy and / or peristomy skin proved to be continuous, with a constant need to adapt to the four adaptive modes, even after months of making it. It becomes necessary to rethink the planning of nursing care in order to adapt the adaptation process to the needs that appear over time, assist in promoting adaptation and, thus, positively interfere with self-care, rehabilitation and quality of life.